Pengaruh Pengungkapan ESG, Profitabilitas dan Likuiditas terhadap Pengambilan Keputusan Investasi Perusahaan - Jessica, Deliana; Arsjah, Regina Jansen (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure, profitability, and liquidity on corporate internal investment decisions. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Investment decisions are measured using capital expenditure intensity, while ESG disclosure is assessed based on secondary ESG scoring data. The study employs a quantitative approach with multiple linear regression analysis. The results reveal that liquidity has a significant positive effect on investment decisions, while ESG disclosure and profitability do not show significant influence. These findings indicate that company management tends to prioritize traditional financial indicators, particularly liquidity, over non-financial factors such as ESG in formulating investment strategies. This research implies that companies need to enhance operational efficiency and integrate ESG into core strategies to make it more impactful on investment decisions. Moreover, ESG disclosure should go beyond compliance and be positioned as a source of strategic value for stakeholders.